Ultrasound can increase biofilm formation by Lactiplantibacillus plantarum and Bifidobacterium spp. - Racioppo, Angela; Speranza, Barbara; Altieri, Clelia; Sinigaglia, Milena; Corbo, Maria Rosaria; Bevilacqua, Antonio (Frontiers in Microbiology, 2023)
The main goal of this research was to the effect of an Ultrasound (US) treatment on biofilm formation of Lactiplantibacillus plantarum (strains c19 and DSM 1055), Bifidobacterium animalis subsp. lactis DSM 10140, B. longum subsp. longum DSM 20219, and B. longum subsp. infantis DSM 20088. At this scope, each microorganism was treated through six US treatments, different for the power (10, 30 or 50% of the net power, 130 W), the duration (2, 6 or 10 min) and the application of pulses (0 or10 s). After the treatment, a biofilm of the strains was let to form on glass slides and the concentration of sessile cells was analyzed for 16 days. Biofilms formed by untreated microorganisms were used as controls. US significantly increased the concentration of sessile cells of B. longum subsp. infantis, while for some other strains US treatment could not affect the formation of biofilm while improving its stability, as found for L. plantarum DSM1055 after 16 days. The variable mainly involved in this positive effect of US was the duration of the treatment, as biofilm formation and stability were improved only for 2 min-treatments; on the other hand, the effect of power and pulses were strain-dependent. The results of this paper are promising, as they suggest practical implication of a US pre-treatment for various fields (improvement of adhesion of microorganisms useful in food or in the gut, biomedical and environmental industries), although further investigations are required to elucidate the mode of action.